Functional and organic dysphonia in voice professionals (lecture) - Julia E. Stepanova (Consilium Medicum, 2023)
An urgent task of otorhinolaryngology (phoniatry) is the diagnosis and treatment of disorders of voice function in voice professionals or persons of voice-speech professions. An undiagnosed laryngeal disease worsens the quality of life of patients, creates difficulties in communication and can even lead to professional unfitness, because the patient does not withstand the necessary vocal load. The leading role in the modern diagnosis of laryngeal diseases belongs to endoscopic research methods video endoscopy and video endostroboscopy. All disorders of voice function are classified as functional and organic. Recent studies have shown that from 30.5 to 40% of voice professionals who have applied for phoniatric care suffer from functional disorders. Functional changes are understood to mean changes in which laryngoscopic examination does not always reveal any visible pathology. But with the help of special research methods, such as stroboscopy (videostroboscopy), spectral analysis of the voice, pathognomonic changes can be determined, and the patient presents characteristic complaints. More often than others, hypotonic and hypo-hypertonic dysphonia are diagnosed. Organic laryngeal diseases are characteristic of 69.5% of patients with dysphonia. They are represented by various nosological forms. Certain difficulties arise in the diagnosis of professional laryngitis and vascular pathology of the larynx. The lecture presents pathognomonic clinical changes of the larynx in voice professionals, knowledge of which is necessary for practical doctors to make a diagnosis.